Alternativa de amostragem para a realização da identificação do perigo da fauna nos aeródromos brasileiros - Silva, Fernando Lopes da (2023)
Upon taking flight, humanity began to experience conflicts hitherto unheard of, and the Wright brothers, pioneers of American aviation, recorded the first occurrence of wildlife hazard in history in 1905 even before the airplane was invented the following year by the Brazilian Alberto Santos Dumont. The development of aviation in the interwar period forced countries to raise levels of aviation organization, which allowed an increase in the flow of transport, with this, conflicts also grew. Lifting, handling and management techniques need to be tested and applied in order to increase operational safety. MCA 3-8 is the main wildlife hazard manual used in Brazil, both by civil and military airports, and this manual contains the procedures related to the achievement of a preliminary approach to identify the problems related to the wildlife of a given airport: Wildlife Hazard Identification (IPF). Is the execution of this procedure restricted to the suggestion in the manual or was it possible to find an alternative? The manual directs the preparation of the IPF by carrying out two wildlife survey samples monthly over the course of a year. The data presented show that an alternative to this sampling model is viable, concentrating the surveys in a shorter period, within each season of the year, without detriment to the sampling effort. In the present study, regardless of whether the data were obtained through monthly or seasonal surveys, the risk matrices indicated the same problem species, even with the same degree of risk, that is, for the main objective of a animal census that will compose an IPF, both proposals for obtaining the data met the needs for the analyses. From the creation of the IPF, the management process is able to be better conducted and the entire prevention chain can occur in a fluid way, with actions and resources being allocated to the right places. In short, airport managers will now be able to have more than one alternative for identifying dangers related to wildlife for air operations within their reality. It will be possible to choose the most viable option so that occurrences involving animals and aircraft are mitigated and all the lives involved are preserved, which is important for both airsafety and conservation.